Analysis Model in the Cloud Optimization Consumption in Pricing the Internet Bandwidt - Indrawati Indrawati; Fitri Maya Puspita; Sri Erlita; Inosensius Nadeak (Institute of Advanced Engineering and Science, 2018)
The problem of internet pricing is a problem that is often a major problem in optimization. In this study, the internet pricing scheme focuses on optimizing the use of bandwidth consumption. This research utilizes modification of cloud model in finding optimal solution in network. Cloud computing is computational model which is like network, server, storage and service that is utilizing internet connection. As ISP's Internet service provider requires appropriate pricing schemes in order to maximize revenue and provide quality of service (Quality on Service) or QoS so as to satisfy internet users or users. The model used will be completed with the help of LINGO software program to get optimal solution and accurate result. Based on the optimal solution obtained from the modification of the cloud model can be utilized ISP to maximize revenue and provide services in accordance with needs and requests.